Likuiditas dalam Kinerja Keuangan Subsektor Perbankan - Lailia, Zana Fitri Nur; Ardiana, Meta (JFAS : Journal of Finance and Accounting Studies, 2024)
This study aims to examine the effect of liquidity on financial performance with capital adequacy as a moderating variable. This type of research is quantitative with a purposive sampling method and the object of research is companies listed on the Indonesia Stock Exchange during the 2020-2021 period, namely the banking subsector. Data analysis using the SmartPLS 4.0.9.2 method. The results of this study prove that liquidity has no effect on financial performance which is indicated by a value of 0.345, meaning that the significant value is greater than 0.05. The interaction of capital adequacy on the liquidity relationship has no effect on financial performance which is indicated by a value of 0.373, meaning that the significant value is greater than 0.05.